Efficacy and safety of 40 mg or 60 mg duloxetine in Japanese adults with diabetic neuropathic pain: Results from a randomized, 52‐week, open‐label study. Issue 1 (18th May 2015) - Yasuda, Hitoshi; Hotta, Nigishi; Kasuga, Masato; Kashiwagi, Atsunori; Kawamori, Ryuzo; Yamada, Tadaaki; Baba, Yuko; Alev, Levent; Nakajo, Ko
Abstract: Introduction: To examine the long‐term efficacy and safety of duloxetine in the treatment of Japanese patients with diabetic neuropathic pain, we carried out a 52‐week, randomized, open‐label extension of a 12‐week, double‐blind, placebo‐controlled study. Materials and Methods: Japanese adults with diabetic neuropathic pain who completed the double‐blind study were eligible for this long‐term study, carried out at 71 sites in Japan (March 2008 to March 2010). Participants ( n  = 258) were re‐randomized (1:1) to 40 mg/day or 60 mg/day duloxetine. Pain (Brief Pain Inventory severity and interference), quality of life (Patient's Global Impression of Improvement), and safety (primary outcome; adverse events, vital signs, metabolic measures) were measured. Results: Significant ( P  < 0.0001) and sustained improvements (change ± standard deviation; n  = 257) were observed in Brief Pain Inventory severity (average pain score −2.1 ± 1.7). Improvements were also seen in Brief Pain Inventory interference (mean of subscores −0.96 ± 1.52) and Patient's Global Impression of Improvement (−0.9 ± 1.1) scores; these scores decreased significantly ( P  < 0.0001) during the long‐term study. Frequently reported adverse events included somnolence (13.6%), constipation (13.2%) and nausea (10.5%). Increases were observed in plasma glucose, glycosylated hemoglobin and total cholesterol levels, and in bodyweight and heart rate; however, none of these were clinically meaningful. Overall, there were no clinically significant safety concerns. Conclusions: This is the first publication of a long‐term study carried out in Asia with an entirely Japanese patient population to suggest that long‐term duloxetine therapy for diabetic neuropathic pain is effective and has an acceptable safety profile. Abstract : To examine the long‐term efficacy and safety of duloxetine in the treatment of Japanese patients with diabetic neuropathic pain, we conducted a 52 week, randomized, open‐label extension of a 12‐week, double‐blind, placebo controlled study. Significant and sustained improvements in Brief Pain Inventory severity scores were observed, with no clinically significant safety concerns. This is the first publication of a long‐term study carried out in Asia with an entirely Japanese patient population to suggest that long‐term duloxetine therapy for diabetic neuropathic pain is effective and has an acceptable safety profile.